Do inhabitants profit from integrating a public health focus in urban renewal programmes? A Dutch case study. - Annemarie Ruijsbroek; Albert Wong; Frank den Hertog; Mariël Droomers; Carolien van den Brink; Anton E Kunst; Hans A M van Oers; Karien Stronks (PLoS ONE, 2022)
Background Urban renewal traditionally involves policy sectors such as housing, transport, and employment, which potentially can enhance the health of residents living in deprived areas. Additional involvement of the public health sector might increase the health impact of these urban renewal activities. This study evaluates the health impact of an additional focus on health, under the heading of Healthy District Experiments (HDE), within districts where an urban renewal programme was carried out. Methods We evaluated changes in health outcomes before the start of the HDE and after implementation, and compared these changes with health changes in control areas, e.g. districts from the urban renewal programme where no additional HDE was implemented. Additionally, we gathered information on the content of the experiments to determine what types of activities have been implemented. Results The additional activities from the HDE were mostly aimed at strengthening the health care in the districts and at promoting physical activity. When we compared the prevalence in general health, mental health, overweight, obesity, smoking, and physical activity during the study period between the HDE districts and control districts, we found no significant differences in the rate of change. The study is limited by a small sample size and the cross-sectional nature of the data. These and other limitations are discussed. Conclusion We found no evidence for a beneficial health impact of the activities that were initiated with a specific focus on health, within a Dutch urban renewal programme. Specific attention for network management and the integration of such activities in the wider programme, as well as an allocated budget might be needed in order to sort a health impact.